Restorative treatment on class I and II restorations in primary molars: A survey of Brazilian dental schools - Motisuki, Cristiane [UNESP]; Lima, Luciana Monti; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Guelmann, Márcio (My University, 2005)
A survey was sent to 70 Brazilian dental schools evaluating techniques and restorative materials being taught for Class I and II preparation in posterior primary teeth by Pediatric Dentistry courses. After a 54% response rate, marked teaching diversity was found among Brazilian dental schools. Amalgam continues to be taught, but a tendency of preference towards more esthetic-like materials was observed.
Keywords: dental alloy; glass ionomer; resin; Brazil; deciduous tooth; dental education; dental surgery; dentistry; education; human; methodology; molar tooth; questionnaire; Composite Resins; Dental Amalgam; Dental Cavity Lining; Dental Cavity Preparation; Dental Restoration, Permanent; Dentistry, Operative; Glass Ionomer Cements; Humans; Molar; Pediatric Dentistry; Questionnaires; Schools, Dental; Tooth, Deciduous